PRECLINICAL COCHLEAR DYSFUNCTION DETECTION THROUGH INTRA-INDIVIDUAL EAR COMPARISON IN HABITUAL MOBILE PHONE USERS: A PURE TONE AUDIOMETRY STUDY AMONG MEDICAL STUDENTS (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Prolonged mobile phone use has generated apprehensions about subtle auditory effects resulting from chronic unilateral exposure to radiofrequency electromagnetic fields (RF-EMF) and acoustic stimulation. Identifying early cochlear dysfunction prior to the manifestation of clinically significant hearing loss continues to be a public health imperative. This study sought to identify preclinical cochlear alterations by comparing hearing thresholds between the predominantly exposed ear and the contralateral ear in habitual mobile phone users. Methods: A cross-sectional observational study was performed. A pretested, structured questionnaire was given to all participants to collect data. Self-reported auditory complaints, such as tinnitus, ear discomfort, or perceived hearing difficulties, were collected within the questionnaire. Tympanometry and pure tone audiometry was conducted as a part of audiology testing. Paired t-test was used to compare the pure tone hearing thresholds of the exposed and unexposed ear. A p-value of less than 0.05 was considered to be statistically significant. Results: At higher and speech-related frequencies, the predominantly exposed ear exhibited significantly increased thresholds (p